Mass Marriage Matchmaking at Pesantren: An Integration of Hadith and Sociological Perspectives - Kusnadi, Kusnadi; Al-Amruzi, M. Fahmi; Adawiyah, Rabiatul; Herianto, Herianto (KARSA Journal of Social and Islamic Culture, 2025)
Marriage in Islamic boarding schools plays a crucial role in shaping students’ religious, social, and moral character. At Pondok Pesantren Hidayatullah Balikpapan, marriage is part of the developmental program for mentally and spiritually prepared students. A distinctive feature is the absence of direct acquaintance between prospective spouses; sometimes, they only view each other’s photographs during administrative procedures. This study aims to understand the matchmaking mechanism at Pesantren Hidayatullah Balikpapan and analyze it from the perspectives of hadith and sociology. This research adopts a qualitative phenomenological approach. Data were collected on-site at Pondok Pesantren Hidayatullah Balikpapan through in-depth interviews, participant observation, and literature review. Purposive sampling was employed to select key informants. Data analysis involved data reduction, information simplification, and conclusion drawing. The study reveals three main findings. First, the initial mass marriage practice proceeded without a taaruf process, with the pesantren directly assigning couples. Second, over time, acquaintances via photographs emerged before the solemnization, and some students began proposing independently. Third, based on hadith, taaruf and viewing one’s prospective spouse are encouraged to foster family harmony. From a sociological standpoint, using Talcott Parsons’s AGIL framework, the practice without taaruf remains effective through social norm adaptation, collective goal attainment, structural integration, and preservation of the Pesantren’s traditional values.